Factors affecting uptake of optimal doses of sulphadoxine-pyrimethamine for intermittent preventive treatment of malaria in pregnancy in six districts of Tanzania - Exavery, Amon (BioMed Central, 2014)
BACKGROUND: Intermittent preventive treatment during pregnancy (IPTp) with optimal doses (two+) of sulphadoxine-pyrimethamine (SP) protects pregnant women from malaria-related adverse outcomes. This study assesses the extent and predictors of uptake of optimal doses of IPTp-SP in six districts of Tanzania. METHODS: The data come from a cross-sectional survey of random households conducted in six districts in Tanzania in 2012. A total of 1,267 women, with children aged less than two years and who had sought antenatal care (ANC) at least once during pregnancy, were selected for the current analysis. Data analysis involved the use of Chi-Square (χ(2)) for associations and multivariate analysis was performed using multinomial logistic regression. RESULTS: Overall, 43.6% and 28.5% of the women received optimal (two+) and partial (one) doses of IPTp-SP respectively during pregnancy. Having had been counseled on the dangers of malaria during pregnancy was the most pervasive determinant of both optimal (RRR = 6.47, 95% CI 4.66-8.97) and partial (RRR = 4.24, 95% CI 3.00-6.00) uptake of IPTp-SP doses. Early ANC initiation was associated with a higher likelihood of uptake of optimal doses of IPTp-SP (RRR = 2.05, 95% CI 1.18-3.57). Also, women with secondary or higher education were almost twice as likely as those who had never been to school to have received optimal SP doses during pregnancy (RRR = 1.93, 95% CI 1.04-3.56). Being married was associated with a 60% decline in the partial uptake of IPTp-SP (RRR = 0.40, 95% CI 0.17-0.96). Inter-district variations in the uptake of both optimal and partial IPTp-SP doses existed (P < 0.05). CONCLUSION: Counseling to pregnant women on the dangers of malaria in pregnancy and formal education beyond primary school is important to enhance uptake of optimal doses of SP for malaria control in pregnancy in Tanzania. ANC initiation in the first trimester should be promoted to enhance coverage of optimal doses of IPTp-SP. Programmes should aim to curb geographical barriers due to place of residence to enhance optimal coverage of IPTp-SP in Tanzania.